Functional Response of Harmonia axyridis to the Larvae of Spodoptera litura: The Combined Effect of Temperatures and Prey Instars - Islam, Yasir; Shah, Farhan Mahmood; Güncan, Ali; DeLong, John Paul; Zhou, Xingmiao (Frontiers in Plant Science, 2022)
Functional responses are central to predator-prey dynamics, describing how predation varies with prey abundance. Functional responses often are measured without regard to prey size (i.e., body mass) or the temperature-dependence of feeding rates. However, variation in prey size within populations is ubiquitous, and predation rates are often both size and temperature-dependent. Here we assessed functional responses of larvae and adult Harmonia axyridis on the 1st, 2nd and 3rd instar of the prey Spodoptera litura across a range of temperatures (i.e., 15, 20, 25, 30 and 35°C). The type and parameters of the functional responses were determined using logistic regression and fitted to the Rogers random predator equation. The magnitude of predation varied with predator and prey stage, but prey predation increased with warming and predator age. Predation by the female and 4th instar H. axyridis on the 1st instar prey was greater, followed by the 2nd and 3rd instar prey S. litura. No predation occurred on the larger prey for the 1st, 2nd and 3rd instar of H. axyridis. The larvae and adult H. axyridis produced a Type II (hyperbolic) functional response curve across all temperatures and the three prey types they consumed. Space clearance rates, handling time, and maximum predation rates of H. axyridis changed with temperature and prey size, increasing with temperature and decreasing with prey size, suggesting more predation will occur on younger prey. This study indicates an interactive role of temperature and prey/predator size in shaping functional responses, which might complicate planning effective biocontrol strategies against this serious pest.